The Effects of Rule of Law, Regulatory Quality, and Renewable Energy on CO2 Emissions in South Asia - Mahmood, Haider; Hassan, Shafiqul; Tanveer, Muhammad; Ahmad, Abdul-Rahim (International Journal of Energy Economics and Policy, 2022)
Governance can help in regulating the environmental quality of any economy. Hence, the present study explores the effects of rule of law and regulatory quality on the CO2 emissions in four South Asian economies from 1996-2019, controlling renewable energy and income level in the model. The results corroborate the Environmental Kuznets Curve (EKC) hypothesis in the long-run analysis of four South Asian economies but renewable energy could not affect the CO2 emissions. Moreover, regulatory quality helps reduce CO2 emissions and shows the technique and/or composition effects in these economies. However, the rule of law has a pre-dominant scale effect in these economies and increases CO2 emissions. Based on the results, we recommend South Asian countries to strengthen the regulatory quality to support a clean environment. Moreover, rule of law needs attention and modifications to have pleasant environmental effects.